EEKSPLORASI ETNOMATEMATIKA PADA SONAF LAN TAOLIN KABUPATEN TIMOR TENGAH UTARA - Trevila Tamnau; Stanislaus Amsikan; Oktovianus Mamoh (SIGMA, 2021)
Learning mathematics using a cultural approach is commonly known as ethnomatematics. Ethnomatematics is a mathematics learning approach that bridges mathematics learning through local culture. The purpose of this study was to explore the culture of Sonaf L.A.N Taolin and describe the mathematical concepts that exist in the building elements of Sonaf L.A.N Taolin. This type of qualitative research uses an ethnographic approach that aims to explore the mathematical concepts found in Sonaf L.A.N Taolin. The subject of this study was an informant, Raja Insana. The research instruments were human instruments, observation guidelines, and interview guides. Data analysis was carried out in three stages, namely data reduction, data display and conclusion drawing. The results of this study indicate that building elements such as poles, doors, and roofs from Sonaf L.A.N Taolin contain geometry concepts that can be implemented as a medium for learning mathematics on the material: flat shapes, spatial structures, similarities, geometric transformations (reflections).